1975
DOI: 10.1021/j100586a011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 spin relaxation and methyl rotation barriers in the methylethylenes

Abstract: Methylethylene Nuclear Relaxation Times 2031 viously reported for this transition. A definitive placement of the 1La band in this crystal, however, will have to await a somewhat higher resolution and probably low-temperature study of the type reported here. Moreover, the location of the band in phenazine itself will have to rest on a more detailed study of the uncomplexed material than has been reported to date.11,15,19 Until such a study has been carried out, it is probably somewhat premature to speculate on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…where TDD is the dipole-dipole relaxation time, TSR is the spin-rotation relaxation time, and T0 is a lumped parameter for all other types of relaxation. Grant et al 13 have shown that T0 is usually negligibly small for systems like those in this study. Fortunately, TDD is directly related9 to and i?c-h (3) so that TDD can be derived from if t)C-h is available.…”
Section: Resultssupporting
confidence: 48%
“…where TDD is the dipole-dipole relaxation time, TSR is the spin-rotation relaxation time, and T0 is a lumped parameter for all other types of relaxation. Grant et al 13 have shown that T0 is usually negligibly small for systems like those in this study. Fortunately, TDD is directly related9 to and i?c-h (3) so that TDD can be derived from if t)C-h is available.…”
Section: Resultssupporting
confidence: 48%
“…Theintegrationoft hese signals shows an uptake of 1.7 isobutene molecules per silver salt (Scheme 4) which is in accordance with the value described in thel iterature. [32] Ac omparison of the 13 CNMR data of the absorbed isobutenew ith values of free isobutene [34] showsasignificant shifto f+ 10 and À12 ppm for the two sp 2 carbon atoms (d = 151.4 ppm (=CMe 2 )a nd 98.4 ppm (H 2 C=)), which strongly indicates an interaction with the silver cation. The stretching vibration of the CÀNb ond in the IR spectrum is observed at 2272 cm À1 ,w hich is decreased by 15 cm À1 relative to 1g.…”
Section: Resultsmentioning
confidence: 95%
“…For all measurements of spin-lattice relaxation the standard 180°--90°pulse sequence was used with the phase of the 90°p ulse changed by 180°on every scan. 13 Except as noted previously2 this pulse sequence was under computer control. Magnetization was taken to be proportional to peak heights which were read manually from recorded spectra.…”
Section: Methodsmentioning
confidence: 96%
“…Accurate utilization of data gathered from biophysical application of l3C methyl probes will potentially require consideration of auto-and cross-correlation effects in both the dipolar and spin-rotation interactions, since spin-rotation frequently plays a role in methyl relaxation. 13 In such a situation analysis of the relaxation is not straightforward, and in the present publication we illustrate an attack on the problem utilizing both and 13C relaxation data.…”
mentioning
confidence: 99%